IDENTIFYING STUDENTS’ WAYS OF LEARNING OF MATHEMATICS AT UNIVERSITY LEVEL - Ramāna, Līga; Veilande, Ingrīda; Zīlīte, Agnese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The Mathematics study course is one of the core subjects in study programs of Technical Universities. To acquire this course successfully it is necessary to have mathematics background of sufficiently high quality. The authors of this paper recognize the difficulties first year students face due of their insufficient mathematical knowledge.Today, universities emphasize independent study work by students and allocate special time slots for this. To be successful, students need to plan their study time, use appropriate learning methods, and have motivation. Because of the significance of students’ individual work, a questionnaire was developed to research how students plan their time and activities for learning mathematics. The authors selected three focus groups of first year students at Riga Technical University (RTU), Latvian Maritime Academy (LMA), and University of Latvia (UL) to collect the data. The comparative analysis of data showed how students use the time slots allocated by institutions. The UL and RTU students on average do not fulfil this time completely, while the LMA students spend more time for learning mathematics. Students highly value individual consultations with teachers; they actively communicate with study mates to solve homework assignments; and students use information technologies in the study process.